A review on rapid responsive energy storage technologies for frequency regulation in modern power systems. (March 2020) - Akram, Umer; Nadarajah, Mithulananthan; Shah, Rakibuzzaman; Milano, Federico
Abstract: A paradigm shift in power generation technologies is happening all over the world. This results in replacement of conventional synchronous machines with inertia less power electronic interfaced renewable energy sources (RES). The replacement by intermittent RES, i.e., solar PV and wind turbines, has two-fold effect on power systems: (i) reduction in inertia and (ii) intermittent generation, lead to the degradation of the frequency stability. In modern power system, the frequency regulation (FR) has become one of the most crucial challenges compared to conventional system because the inertia is reduced and both generation and demand are stochastic. The fast responsive energy storage technologies, i.e., battery energy storage, supercapacitor storage technology, flywheel energy storage, and superconducting magnetic energy storage are recognized as viable sources to provide FR in power system with high penetration of RES. The important aspects that are required to understand the applications of rapid responsive energy storage technologies for FR are modeling, planning (sizing and location of storage), and operation (control of storage). This paper comprehensively reviews these important aspects to understand the applications of fast responsive storage technologies more effectively for FR services. In addition, based on the real world experiences this paper highlights the gaps and limitations in the state-of-the-art practices. Moreover, this study also provides recommendations and future directions for researchers working on the applications of storage technologies providing FR services. Highlights: Review of technological solutions for frequency regulation (FR) in modern power systems. Review of grid codes relating for FR by major electricity market operators. Comprehensive review of modelling of rapid responsive energy storage systems (ESS). Comprehensive review of planning and operation of rapid responsive ESS for FR. Limitations on applications of rapid responsive ESS for FR and possible solutions.